Nucleophilic substitution at a coordinatively saturated five-membered NHC center dot haloborane centre - Kundu, Gargi; Tothadi, Srinu; Sen, Sakya S. (Inorganics, 2022)
In this paper, we have used a saturated five-membered N-Heterocyclic carbene (5SIDipp = 1,3-bis-(2,6-diisopropylphenyl)imidazolin-2-ylidine) for the synthesis of SNHC-haloboranes adducts and their further nucleophilic substitutions to put unusual functional groups at the central boron atom. The reaction of 5-SIDipp with RBCl2 yields Lewis-base adducts, 5-SIDipp center dot RBCl2 [R = H (1), Ph (2)]. The hydrolysis of 1 gives the NHC stabilized boric acid, 5-SIDipp center dot B(OH)(3) (3), selectively. Replacement of chlorine atoms from 1 and 2 with one equivalent of AgOTf led to the formation of 5-SIDipp center dot HBCl(OTf) (4) and 5-SIDipp center dot PhBCl(OTf) (5a), where all the substituents on the boron atoms are different. The addition of two equivalents of AgNO3 to 2 leads to the formation of rare di-nitro substituted 5-SIDipp center dot BPh(NO3)(2) (6). Further, the reaction of 5-SIDipp with B(C6F5)(3) in tetrahydrofuran and diethyl ether shows a frustrated Lewis pair type small molecule activated products, 7 and 8.
Keywords: NHC-haloboranes; nucleophilic substitution; saturated NHC; tetra-coordinate boron